The classification of a Sesbania sesban (ssp. sesban) collection. I. Morphological attributes and their taxonomic significance - Heering, J.H.; Nokoe, S.; Jemal, M. (1996)
A collection of 108 accessions of Sesbania sesban (Fabacea, Papilionoideae) was grown in the field and classified using morphological attributes. Numerical analysis resulted in the division of the collection into 2 major groups, which corresponded to the different varieties that exist in the subspecies sesban. The varieties sesban and bicolor could be distinguished from variety nubica mainly on the basis of their leaflet number and size, seed size, seed colour and growth habit. The variety nubica could be further subdivided into 5 groups by both the average linkage and the Partitioning Around Medoids (PAM) algorithms. The average linkage algorithm differentiated accessions mainly on the basis of quantitative characters, whereas the PAM method used qualitative attributes for grouping accessions. This classification will assist in the selection of germplasm for further evaluation and/or breeding.